2017
DOI: 10.1504/ijicot.2017.083827
|View full text |Cite
|
Sign up to set email alerts
|

The combinatorics of LCD codes: linear programming bound and orthogonal matrices

Abstract: Linear Complementary Dual codes (LCD) are binary linear codes that meet their dual trivially. We construct LCD codes using orthogonal matrices, self-dual codes, combinatorial designs and Gray map from codes over the family of rings R k . We give a linear programming bound on the largest size of an LCD code of given length and minimum distance. We make a table of lower bounds for this combinatorial function for modest values of the parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 9 publications
1
68
0
Order By: Relevance
“…In this section we consider binary codes. Recently, Galvez et al [22] obtain the exact values of LD(n, k) for k = 2 and arbitrary n. By Theorem 1 in [22], we know that there exist LCD codes with LD(n, 2) = ⌊ 2n 3 ⌋ only for n ≡ 1, ±2, 3 (mod 6). An [n, k, d] linear code is optimal if the minimum distance achieve the Gresmer Bound.…”
Section: The Enumeration Of [N 2 D] Binary Optimal Lcd Codesmentioning
confidence: 97%
See 1 more Smart Citation
“…In this section we consider binary codes. Recently, Galvez et al [22] obtain the exact values of LD(n, k) for k = 2 and arbitrary n. By Theorem 1 in [22], we know that there exist LCD codes with LD(n, 2) = ⌊ 2n 3 ⌋ only for n ≡ 1, ±2, 3 (mod 6). An [n, k, d] linear code is optimal if the minimum distance achieve the Gresmer Bound.…”
Section: The Enumeration Of [N 2 D] Binary Optimal Lcd Codesmentioning
confidence: 97%
“…The combinatorial functions LD(n, k) and LD(n, d) has been introduced and studied by Dougherty et al [22] and Galvez et al [17]. The definitions of LD(n, k) and LD(n, d) as follows, we will use them frequently in the rest of this paper.…”
Section: Preliminariesmentioning
confidence: 99%
“…al. developed a linear programming bound on the largest size of an LCD code of given length and minimum distance [9]. Guneri et.…”
Section: Introductionmentioning
confidence: 99%
“…In their work, they presented several constructions of LCD codes and showed that non-binary LCD codes in characteristic 2 can be transformed into binary LCD codes by expansion. For further recent research on the topic we refer the reader to [2,12,15,28]. One of our main challenges is to construct LCD codes over finite fields that also have good error correcting properties.…”
Section: Introductionmentioning
confidence: 99%